Tamil Migration to Colonial Malay and Burma from 1880-1920: Analysing the Acculturation Process through the Lens of Fashion - Ananya Athaiya (International Journal of Trends in Humanities, 2024)
This paper seeks to understand the cultural repercussions of colonial labour migration, which emerged as one of the key characteristics of the 19th century as European nations set up colonies in parts of Africa, Latin America, and South and Southeast Asia. The ‘coolie’ market consisted of indentured labourers and slaves and allowed the colonial rulers to supplement labour in new colonies. As the labourers migrated to new lands, they carried with them their culture in the form of religious, food and clothing practices. They underwent various degrees of acculturation that often resulted in integration, exchange or assimilation of ideas and practices between the host groups and the migrant communities. This study sheds light on the acculturation process between Tamil labourers and host groups from the British colonies of Malay and Burma from 1880-1920 as it took place through clothing practices. By making use of visual and textual evidence, it seeks to understand the cultural exchange between colonised communities in British territories and the dynamics of power that affected the acculturation process. It observed that there was significant mutual influence, however, the degree of such influence differed in both colonies owing to a variety of other political, social and economic factors. The nature of the host communities was a critical factor in determining the extent of acculturation as well as the political standing of key native players. The constitution of the migrants- their socio-economic background and their motivations for migration- also played a significant role in dictating the degree of acculturation between different groups.
Keywords: Colonial migration; acculturation; clothing; post colonialism; south and southeast asia